Zikir dan Ketenangan Jiwa: Studi Jamaah Tarekat Desa Rawa Jaya, Merangin - Wuri Septi; Sandi Maspika; Madyan Madyan (JIGC (Journal of Islamic Guidance and Counseling), 2021)
this research is motivated by some people who adhere to the Nahdatul Ulama who consider zikir to be very important in everyday life besides getting closer to Allah SWT, zikir can also provide peace of mind, considering that in today’s life there are many templations and trials in everyday life. The community accepts without any rejection because the teachings of the tarekat are many zikir prectices to get closer to Allah SWT. There is a practice for someone who follows the tarekat A person who has not followed the tarekat then the practice be gets s still practiced in his daily life that has no effect on him. This happened because he had broken the allegiance (promise) of a student with his teacher. This study used a quantitative study which took a sample of 60 respondents. The data in this study the authors obtained by using an instrument in the form of a questionnaire result were analyzed using a simple linear regression formula, using the help of the SPSS 26 computer program. Based on the data obtained in the research and data analysis through the calculation of thr questionnaire score, the effect of zikir naqsyabandiyah on mental peace in tarekat congregations obtained 14,78 while at 5% significance level wa 3,16. The results of the correlation of this study indicate that there is a significant effect of zikir tarekat naqsyabandiyah on mental peace among tarekat congregations in Rawa Jaya Village. As evidenced